2020
DOI: 10.1155/2020/5672048
|View full text |Cite
|
Sign up to set email alerts
|

Unresectable Hepatic Metastasis of Uveal Melanoma: Hepatic Chemosaturation with High-Dose Melphalan—Long-Term Overall Survival Negatively Correlates with Tumor Burden

Abstract: Introduction. Percutaneous hepatic perfusion with melphalan (PHP-M) for hepatic metastasis of uveal melanoma (LMUM) achieves high local response rates, but the individual clinical benefit is poorly defined. We aimed to determine cofactors of response and clinical outcomes including the probability of long-term (5-years) overall survival (OS) in PHP-M-treated patients with LMUM. Patients and Methods. We retrospectively reviewed clinicopathological, radiological, and outcome data of 19 patients with unresectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 28 publications
5
19
0
6
Order By: Relevance
“…Our results suggested that the perioperative management of PHMP is frequently associated with procedure-related issues. These findings are in similarity with previous studies from other centers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The main issues related to PHMP were hemodynamic depression, vascular access complications, and coagulopathy.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results suggested that the perioperative management of PHMP is frequently associated with procedure-related issues. These findings are in similarity with previous studies from other centers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The main issues related to PHMP were hemodynamic depression, vascular access complications, and coagulopathy.…”
Section: Discussionsupporting
confidence: 90%
“…Hemodynamic instability, particularly during balloon occlusion and melphalan wash-in, required advanced anesthetic expertise. We frequently observed large intraindividual ranges of SBP and heart rate, which were similar to previous studies that have reported significant transient hypotension during hemofiltration [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Hence, patients scheduled for PHMP should present with appropriate cardiovascular fitness and without pathologies of the brain-supplying vessels to avoid cerebral ischemia.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations